Financial Performance Analysis Of Customer Intensity In Using Fintech P2p Lending Services At Pt Pasar Dana Pinjaman And Pt Akulaku Finance Indonesia - Fazriansyah, Fazriansyah; Harahap, Lily Rahmawati; Aryanti, Rahmi (Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the effect of the intensity of use of P2P lending fintech services by customers on the financial performance of PT. Pasar Dana Pinjaman and PT. Akulaku Finance Indonesia. This research approach uses quantitative and qualitative methods. Quantitative data were obtained from the financial reports of both companies for the period 2020–2023 and analyzed using financial ratios (profitability, liquidity, solvency, and activity). Qualitative data were obtained by distributing questionnaires to 100 millennial and Gen Z respondents in Palembang City who had used online loan services. Statistical tests using the Independent Sample t-test were used to see the differences in financial performance between the two companies.The results of the study show that the intensity of use of online loan services affects the company's financial performance. PT. Akulaku Finance Indonesia shows a more stable and profitable financial performance compared to PT. Pasar Dana Pinjaman, especially in terms of profitability and solvency ratios. There are significant differences in several financial indicators between the two companies. Respondents showed high interest in using fintech lending because of the ease of access and speed of service, although there are still concerns about data security and long-term debt risks.